Determinants Of Murabaha Margin Income Of Islamic Commercial Banks In Indonesia - Hasibuan, Abdul Nasser; Hardana, Ali (JPS (Jurnal Perbankan Syariah), 2024)
This research aims to analyze and show the influence of overhead costs, risk costs and Wadiah savings on Murabaha margin income at Islamic commercial banks (ICB) in Indonesia. This research method uses a quantitative approach, and the data used is secondary data. The population of this study was ICB for 2020-2023. The sampling technique used purposive sampling to obtain a sample of 8 ICB with 32 observation data. Data collection techniques in this research used documentation and a literature study. The data analysis technique uses multiple linear regression. The results of this research indicate that overhead costs have a positive effect on Murabaha's margin income. Risk costs do not affect Murabaha's margin income. Wadiah's savings have a positive effect on Murabaha's margin income. The results of this research can complement existing theories and become a reference for future research. Then, it can become a reference for ICB in increasing the amount of Murabaha's margin income through increasing overhead costs and Wadiah savings, as well as reducing risk costs collected from the community.